Aspergillosis infections and the lung - Barnes, Rosemary (Henry Stewart Talks, 2013)
Pulmonary aspergillosis, Invasive disease, Clinical diagnosis, Treatment and management strategies, Aspergillus in the ICU, Chronic aspergillosis